Pengaruh Pelatihan Berbasis Teknologi Terhadap Peningkatan Keahlian Profesional Teologi Kristen - Edward Nimits Abraham; Eunike Eunike; Lucky Antonio; Matius Kala'tiku; Ipan Morris Pangaribuan; Mulianto Mulianto (Sekolah Tinggi Teologia Kerusso Indonesia, 2020)
Facing the challenges of an increasingly developing era, changes will continue to occur in all aspects of life, including one in the world of education. A study needs to be conducted to anticipate increasingly rapid developments, both in Christian and secular theological education. The influence of the challenges of the era will create positive and negative changes, for that it is necessary to conduct an investigation in a study. This study was conducted to investigate the influence of technology-based training on improving professional skills in the field of Christian theology. Integrating the influence of technology-based training in Christian theological education can be an effective strategy for developing relevant and competitive professional skills. Professional skills in the field of Christian theology are an important component for the development of Christian theological education and spiritual understanding of Christian theology. This study is expected to contribute to the development of effective curriculum programs in theological education in the future. The research method used is qualitative with an interview system and questionnaires for training participants. This study shows that the influence of formal technology-based training plays an important role in improving professional skills in the field of Christian theology.